Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China - Loktionov, Valery M.; Lelej, Arkady S.; Xu, Zaifu (Zootaxa, 2017)
The genus Eopompilus Gussakovskij, 1932 is reviewed. A new species, Eopompilus pseudominor Loktionov, Lelej & Xu, sp. nov. is described and illustrated from China, Yunnan. A new synonymy is proposed for E. minor Gussakovskij, 1932 =E. minor itoi Ishikawa, 1965, syn. nov. A lectotype of E. orientalis Gussakovskij, 1932 is designated. The distribution of E. minor Gussakovskij and E. luteus Lelej is enlarged to include China. Araneus ventricosus (L. Koch) (Araneae, Araneidae) is a newly recorded host for E. luteus. An updated diagnosis of the genus Eopompilus, and key to females and males are given.